Exploring English Language Learning via ChatGPT: A Case Study from A Self Determination Theory Perspective - Yusriani, Yusriani; Fithriani, Rahmah (FKIP - Universitas Riau, 2025)
This study aims to explore students' perceptions of using ChatGPT as a tool for learning English grammar, particularly in academic writing. Using a qualitative case study approach, twenty undergraduate students majoring in English education at a state university in North Sumatra were selected through purposive sampling based on their prior experience with ChatGPT, especially in completing assignments for courses like Basic Structure. Data were collected through a Likert-scale questionnaire and semi-structured interviews with four selected participants. The questionnaire data were analyzed quantitatively using frequency counts, while the interview transcripts were analyzed thematically through a three-stage coding process. The findings indicate that ChatGPT supports students’ understanding of grammar by providing instant feedback, contextual explanations, and a flexible learning environment, which in turn boosts their confidence in using English. Within the framework of Self-Determination Theory (SDT), ChatGPT fulfills the needs for competence and autonomy; however, it still falls short in addressing the need for relatedness, which requires meaningful human interaction in the learning process.